Writer. (Krung Thēp : Nittayasān Raitœ̄, 2011)
On contemporary Thai literature, history and criticism.
Description based on: pī thī 1, chabap thī 1 (Karakadākhom 2553 [July 2011])
In Thai.
Keywords: Thai literature -- History and criticism -- Periodicals